Asymmetric ion transport through heterogeneous bilayers of covalent organic frameworks - Xiaopeng Zhang; Shixian Xin; Qin Qian; Xiaoyi Xi; Munan Fang; Zhifei Sun; Yunyang Wang; Yulong Li; Yue Wang; Xingtao Tian; Yuntong Li; Siyu Wang; et al. (NPG Asia Materials)
Abstract In recent years, with the development of interfacial polymerization methodologies, the successful preparation of covalent organic framework (COF) monolayers featuring ultrahigh pore density and molecule-scale thickness has become a reality. This advancement has enabled ion transport with ultrahigh flux across extremely short paths. Owing to these processes, the COF monolayers have shown wide potential applications ranging from energy conversion and artificial mechanosensing to ion sieving. To date, nanofluidic systems based on COF monolayers are homogeneous, leading to nearly symmetric ion transport properties. Studies on the ionic transport behavior within ultrathin COF heterojunctions are limited and remain challenging. Herein, using a two-step sequential self-assembly and subsequent interfacial polymerization strategy, bi-layered heterogeneous tetraphenylporphyrin-based COF membranes composed of negatively charged and positively charged monolayers were prepared. Using an electric field as a driving force, rectified ion transport was observed for the first time. Notably, this ionic current rectification property could be modulated by the salt concentration and the structural composition of the membrane, and it was universal for various COF heterojunctions with different chemical ingredients. These findings are beneficial for promoting the development of innovative nanofluidic materials and devices.